Exploratory factor analysis in establishing dimensions of intervention programmes among obstetric vesicovaginal fistula victims in Northern Nigeria - Nasiru, Muhammad Anka; Md Dahlan, Nuarrual Hilal (Advance Scientific Research, 2020)
Obstetric vesicovaginal fistula (VVF) is a birth-related injury that leads to uncontrollable urine leakage via the vagina. Recently, the Nigerian government has implemented several intervention programmes (IVP) to encourage fistula women to seek treatment. However, despite the government's effort, the number of victims who turn out for cureis not encouraging. Earlier studies were unable to integrate appropriate IVP and explore the various dimension and factor loadings of IVP in health-seeking behaviour. Thus, this study's objective was to analyse the diverse dimensional components and factors loading of IVP and its influence on health-seeking behaviour among VVF women. This study utilized a cross-sectional survey design and SPSS software v23.A total of 321 questionnaires were administered, 302 were valid for onwards analysis. The study’s result showe done component with eigen value exceeding 1.Also, two components emerged from the report, namely rehabilitation and campaign programmes. Additionally, the loadings of the15 items in the components ranged from 0.66-0.89. Moreover, the correlation matrix of the construct’s items has a coefficients correlation values of 0.3 and above, indicating that the items are not highly correlated. Furthermore, the construct's reliability was accepted since the result showed Cronbach’s alpha value of .73.Similarly, the construct validity was significant since the percentage of variance explained (AVE) was 76.0%. Besides, the Kaiser-Meyer-Olkin (KMO) measure of sampling adequacy was satisfactory at 0.94. Also, Bartlett's test of sphericity was significant statistically, at 0.00. Based on the preceding result, the study indicated appropriate intervention programmes, especially rehabilitation, inspired health-seeking behaviour among VVF women in northern Nigeria. Precisely, this study shows that by enforcing proper laws and policies regarding the use of maternal and child healthcare programmes, several victims of fistula will seek a cure. Also, providing robust funding, leadership, and governance that allows for supervision and accountability encourages the VVF centres to offer intervention programmes and emergency transportation services for the victims with VVF emergencies, among others, facilitate the implementation of effective IVP. Consequently, this study recommends that administrators and policymakers should focus attention on improving the rehabilitation and campaign programs elements, including ree-surgery, skills acquisition, an educational campaign, and girl-child education.